Downward trends in acute myocardial infarction incidence: how do migrants fare with the majority population? Results from a nationwide study. (December 2014) - van Oeffelen, AAM; Agyemang, C; Koopman, C; Stronks, K; Bots, ML; Vaartjes, I
Aims: In previous decades, a steep decline in acute myocardial infarction (AMI) incidence occurred in Western countries. We assessed whether this decline was also present in migrant groups living in the Netherlands. Methods and results: Nationwide registers were linked between 1998 and 2007. Poisson regression analyses were used to calculate the biannual percentage change in AMI incidence within major non-Western migrant groups, and the differences in these changes with the Dutch majority population. Within the Dutch majority population, AMI incidence significantly declined in men (−12%) and women (−9.5%). Incidence also declined among most migrant groups under study, ranging from −12 to −4.0% in men, and from −16 to −9.5% in women. Only in Turkish women and Moroccan men the AMI incidence remained stable over time (−0.3 and 2.8%, respectively). There were no statistically significant trend differences between the Dutch majority population and the migrant groups under study. The higher AMI incidence in Turkish men and Surinamese men and women, and the lower AMI incidence in Moroccan men persisted over time. Conclusions: There was a declining AMI incidence rate within the Dutch majority population as well as within most of the major migrant groups living in the Netherlands, except in Turkish women and Moroccan men. Trend patterns among migrant groups did not significantly differ from the Dutch majority population. To reduce ethnic inequalities, primary preventive strategies should be targeted at those migrant groups with a persisting higher incidence.